A $$O(\log n)$$ Distributed Algorithm to Construct Routing Structures for Pub/Sub Systems: Regular Submission - Turau, Volker (Stabilization, Safety, and Security of Distributed Systems, 2018)
The Industrial Internet of Things relies on event-driven services that run on wireless networks using low power protocols. The loose coupling and the inherent scalability make publish/subscribe systems an ideal candidate for such systems. This work introduces a new routing structure for such systems and an efficient distributed algorithm to build this structure. This routing structure supports all features of PSVR, a recently introduced publish/subscribe Middleware for IIoT applications. Provided the density of the underlying communication graph is sufficiently high, each node can be reached using at most $$O(\log n)$$ hops. The algorithm is analyzed for random graphs and we prove that w.h.p.  the data structure can be built in $$O(\log n)$$ synchronous rounds.